2014
DOI: 10.1016/j.enzmictec.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Expression of dehydratase domains from a polyunsaturated fatty acid synthase increases the production of fatty acids in Escherichia coli

Abstract: Increasing the production of fatty acids by microbial fermentation remains an important step towards the generation of biodiesel and other portable liquid fuels. In this work, we report an Escherichia coli strain engineered to overexpress a fragment consisting of four dehydratase domains from the polyunsaturated fatty acid (PUFA) synthase enzyme complex from the deep-sea bacterium, Photobacterium profundum. The DH1-DH2-UMA enzyme fragment was excised from its natural context within a multi-enzyme PKS and expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This postulated third mechanism is suggested by several studies. First, an E. coli recombinant expressing the DNA sequence region covering the DH domain of the P. profundum SS9 pfaC gene was shown to be capable of producing up to a 5-fold increase in TFAs over the negative control, although the dehydration reaction had not previously been identified as a limiting step in bacterial fatty acid biosynthesis [ 30 ] and overexpression of the native dehydratase from E. coli , FabA, did not increase the production of fatty acids [ 31 ]. Therefore, it was proposed that this DH domain also catalyzes the reaction of thioester hydrolysis (TE activity).…”
Section: Organization and Function Of The Pfa Gmentioning
confidence: 99%
“…This postulated third mechanism is suggested by several studies. First, an E. coli recombinant expressing the DNA sequence region covering the DH domain of the P. profundum SS9 pfaC gene was shown to be capable of producing up to a 5-fold increase in TFAs over the negative control, although the dehydration reaction had not previously been identified as a limiting step in bacterial fatty acid biosynthesis [ 30 ] and overexpression of the native dehydratase from E. coli , FabA, did not increase the production of fatty acids [ 31 ]. Therefore, it was proposed that this DH domain also catalyzes the reaction of thioester hydrolysis (TE activity).…”
Section: Organization and Function Of The Pfa Gmentioning
confidence: 99%
“…The PUFA synthase is made of three large subunits with three DH domains. One DH domain that is located in the C‐terminal region of subunit‐A shares more sequence similarity to DH domains of polyketide synthases, while the other two DH domains that reside adjacently in subunit‐C are more similar to Escherichia coli DH FabA (Oyola‐Robles et al ., 2014; Xie et al ., 2018; Hayashi et al ., 2019b). Our recent studies showed that two FabA‐like DH domains can functionally complement E .…”
Section: Introductionmentioning
confidence: 99%
“…According to one report, an Escherichia coli strain engineered to overexpress a fragment consisting of four DH domains from the PUFA synthase enzyme complex, and the results showed that the E . coli strain expressing the DH tetradomain fragment was capable of producing up to a five-fold increase in total fatty acids over the negative control strain lacking the recombinant enzyme [38]. Cao et al engineered an efficient producer of unsaturated fatty acids by overexpressing two genes ( fabA and fabB ) associated with unsaturated fatty acid synthesis in E .…”
Section: Discussionmentioning
confidence: 99%